2020
DOI: 10.1007/978-3-030-29553-0_84-1
|View full text |Cite
|
Sign up to set email alerts
|

School Leaders, Emotional Intelligence, and Equitable Outcomes in Urban Education

Abstract: With the nation's public schools serving a more diverse student population than ever before, the role of the school leader is becoming increasingly complex. Research indicates principal preparation programs are inadequately preparing leaders to address the systemic inequities hindering non-White students' achievement. Administrators in urban public schools face particularly well-documented equity challenges. Providing urban school leaders with the tools to navigate the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…These studies suggest that teachers who have higher levels of administrative support (L. B. Anderson, 2007; Boyd et al, 2011; Flamini et al, 2020) and teachers who receive mentoring are less likely to leave teaching (Hahs-Vaughn & Scherff, 2008; Redding & Smith, 2016). Similarly, other studies have shown that teachers were responsive to salary supplements and retention bonuses targeting low-income schools and districts, often with benefits for student outcomes (e.g., Clotfelter et al, 2008; Henry et al, 2010; Springer et al, 2016; Swain et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that teachers who have higher levels of administrative support (L. B. Anderson, 2007; Boyd et al, 2011; Flamini et al, 2020) and teachers who receive mentoring are less likely to leave teaching (Hahs-Vaughn & Scherff, 2008; Redding & Smith, 2016). Similarly, other studies have shown that teachers were responsive to salary supplements and retention bonuses targeting low-income schools and districts, often with benefits for student outcomes (e.g., Clotfelter et al, 2008; Henry et al, 2010; Springer et al, 2016; Swain et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there is still much work to do in examining the distribution of teacher quality and how it affects postsecondary outcomes across student subgroups. We find scant literature investigating how prepared teachers are to serve in low-income and hyper marginalized school contexts, which might be a factor in current teacher sorting patterns (Carter-Andrews, 2009;Flamini et al, 2020;Freedman & Appleman, 2009;Vagi et al, 2019). To date, policy efforts seeking to solve staffing problems in underserved schools have been primarily informed by scholarship emphasizing financial incentives to recruit (Ingersoll & May, 2011) and retain (Swain et al, 2019) promising teachers in high-poverty schools.…”
Section: Directions For Future Researchmentioning
confidence: 99%